Q. 175.0( 4 Votes )

<span lang="EN-US

Answer :

2x2 + 5x + 3


Factorizing the equation and taking 2x and 3 as common,


= 2x2 + 2x + 3x + 3


= 2x(x +1) + 3(x + 1)


= (2x + 3)(x + 1).

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Factorize each ofRD Sharma - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Factorize each ofRD Sharma - Mathematics

10p2 +RS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics